2018
DOI: 10.1108/jmhtep-08-2016-0039
|View full text |Cite
|
Sign up to set email alerts
|

A deliberative study into the impact of integration on mental health social work in England: merely a dialogue or activism?

Abstract: Purpose The purpose of this paper is twofold. First, to examine the impact on mental health social work of integrated care; and second, to explore the effectiveness of the use of deliberative research, a methodology which is new to mental health social work research. Design/methodology/approach Developed to enable examination of policy, deliberative research is underpinned by a desire to permit choice and change brought about through an iterative dialogue. This communication is based on informed and respectf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Throughout the development process, all parties, especially the government and the community, engage in reciprocal exchanges of messages or aspirations from the development planning stage through implementation and evaluation (Ilu & Olawale, 2014;Odoom, 2020;Wilkins, 2014). As a form of participatory communication, Development Planning Deliberation (DPD) involves all stakeholders/development actors, such as the government, civil society, and private sectors, in a series of interactions, lobbying, negotiation, or transactions to achieve mutual understanding and agreement regarding development planning formulated based on mutual problems, interests, and needs (Jain et al, 2022;Lowenstein, 2020;Palacios, 2016;Tian et al, 2023;Treisman et al, 2016;Vicary & Bailey, 2018;Zhao & Derudder, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Throughout the development process, all parties, especially the government and the community, engage in reciprocal exchanges of messages or aspirations from the development planning stage through implementation and evaluation (Ilu & Olawale, 2014;Odoom, 2020;Wilkins, 2014). As a form of participatory communication, Development Planning Deliberation (DPD) involves all stakeholders/development actors, such as the government, civil society, and private sectors, in a series of interactions, lobbying, negotiation, or transactions to achieve mutual understanding and agreement regarding development planning formulated based on mutual problems, interests, and needs (Jain et al, 2022;Lowenstein, 2020;Palacios, 2016;Tian et al, 2023;Treisman et al, 2016;Vicary & Bailey, 2018;Zhao & Derudder, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Within multidisciplinary teams they have been reported to support their non-social work colleagues to ensure the delivery of support that places the service user and their social and familial networks at the heart of practice, providing non-judgemental, strengthsbased input that promotes self-determination and long-term recovery (Abendstern et al, 2014(Abendstern et al, , 2020Allen, 2014;All-Party Parliamentary Group on Social Work, 2016). Evidence from service users and carers suggests that they value social workers for their ability to see them 'in the round', to work in partnership with them, and to provide clear communication (Allen, 2014;Kam, 2019;Vicary & Bailey, 2018;Wilberforce et al, 2019). Service users have reported that social workers, when compared with their health colleagues, deliver more personcentred support (Boland et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Boundary spanning requires professionals to take on so-called generic roles and tasks alongside those that are considered specific to their profession and others that might have traditionally been regarded as the domain of another professional group. Neither boundary spanning nor generic working have, however, been universally welcomed to date with the erosion of boundaries between professional groups, referred to by Brown et al as 'creeping genericism' (2000, p. 426) leading at times to role entrenchment (Vicary & Bailey, 2018). Those arguing against generic practice cite the loss or underuse of specialist knowledge and skills to the detriment of the service user.…”
Section: Introductionmentioning
confidence: 99%
“…However, whether these efforts have led to consolidation of understanding around specialist social work roles in mental health is unclear. For now, crystallising and protecting the distinct mental health social work role remain problematic (Vicary and Bailey, 2018;Morriss, 2017) Curiously, for a profession dedicated to empowering service users and carers, comparatively few empirical studies have investigated their perspectives of social work (Kam, 2019). In part, this gap may reflect the difficulties that service users have had in establishing a voice in academic circles (Beresford, 2013).…”
Section: Introductionmentioning
confidence: 99%